2003
DOI: 10.1161/01.atv.0000069624.55424.61
|View full text |Cite
|
Sign up to set email alerts
|

Fibroblast Growth Factor-2, But Not Vascular Endothelial Growth Factor, Upregulates Telomerase Activity in Human Endothelial Cells

Abstract: Objective-Telomerase plays a major role in the control of replicative capacity, a critical property for successful angiogenesis and maintenance of endothelial integrity. In this study, we examined the relationship between telomerase activity and endothelial cell proliferation as well as the regulation of this enzyme by fibroblast growth factor-2 (FGF-2) and vascular endothelial growth factor-A (VEGF). Methods and Results-Telomerase was repressed in endothelial cells freshly derived from intact endothelium, whe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
51
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 75 publications
(55 citation statements)
references
References 33 publications
4
51
0
Order By: Relevance
“…The mechanism whereby ACEI promote TERT, in the present conditions, seems to be related to the activation of the FGF-2 pathway, because its silencing or neutralization abrogates TERT expression. Although the evidence indicating down-regulation of telomerase by oxidative stress is overwhelming (Haendeler et al, 2004;Voghel et al, 2008;Erusalimsky and Skene, 2009), interventions that favor its up-regulation are limited to NO donor drugs (Vasa et al, 2000), statins (Haendeler et al, 2004), low-dose aspirin (Hu et al, 2008), estrogen (Grasselli et al, 2008), and FGF-2 (Kurz et al, 2003). The direct stimulation of human TERT expression by NO, either endogenously produced or delivered by NO donor agents as shown here, has recently been disputed (Erusalimsky and Skene, 2009).…”
Section: Discussionmentioning
confidence: 90%
“…The mechanism whereby ACEI promote TERT, in the present conditions, seems to be related to the activation of the FGF-2 pathway, because its silencing or neutralization abrogates TERT expression. Although the evidence indicating down-regulation of telomerase by oxidative stress is overwhelming (Haendeler et al, 2004;Voghel et al, 2008;Erusalimsky and Skene, 2009), interventions that favor its up-regulation are limited to NO donor drugs (Vasa et al, 2000), statins (Haendeler et al, 2004), low-dose aspirin (Hu et al, 2008), estrogen (Grasselli et al, 2008), and FGF-2 (Kurz et al, 2003). The direct stimulation of human TERT expression by NO, either endogenously produced or delivered by NO donor agents as shown here, has recently been disputed (Erusalimsky and Skene, 2009).…”
Section: Discussionmentioning
confidence: 90%
“…Accordingly, the study of the transcriptional changes occurring in cultured endothelial cells revealed that, together with a cluster of angiogenesisrelated genes that were similarly modulated by FGF2 and VEGF, the two growth factors affected the expression of distinct subsets of transcripts [107,108]. Accordingly, FGF2, but not VEGF, induces the upregulation of telomerase activity in endothelial cells, thus preventing the early onset of senescence [109]. Distinct patterns of vascular morphology upon FGF2 or VEGF stimulation are described also in the quail embryo CAM assay [86].…”
Section: Fgf/vegf Cross-talkmentioning
confidence: 99%
“…Aliquots of the cleared lysate equivalent to 2×10 4 cells were assayed for telomerase activity by a modified telomeric repeat amplification protocol (TRAPeze, Intergen, Oxford, UK), as previously described (Kurz et al, 2003). The activity of each sample was calculated from the ratio of the intensity of the telomeric repeat ladder (starting at 50 bp) to the 36 bp internal standard.…”
Section: Bal31 Digestionmentioning
confidence: 99%